2019
DOI: 10.1177/1064804619843384
|View full text |Cite
|
Sign up to set email alerts
|

Does Minimalist Footwear Design Aid in Postural Stability and Fall Prevention in Ergonomics?

Abstract: The purpose of the article is to identify if novel footwear design could aid in postural stability and fall prevention in workplace. Footwear design has been reported to aid the task of maintaining postural stability or balancing in an erect stance while minimizing risk of falls. Minimalistic footwear that has design features such as low mass, lower heel height, and thin midsole can positively influence postural stability. Minimalistic military footwear has been shown to lower incidences of falls with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Figure 1 depicts the results of the systematic search and selection process, including a summary of reasons for exclusion of full text articles, which are further detailed in Supplementary File S2 . The 50 articles to inform the review included 25 quasi-experimental studies [ 2 , 7 , 8 , 9 , 10 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ], eight cross-sectional [ 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ], four randomised control trials [ 55 , 56 , 57 , 58 ], three cohort studies [ 59 , 60 , 61 ], three narrative reviews [ 62 , 63 , 64 ], three systematic reviews [ 13 , 65 , 66 ], three conference abstracts [ 67 , 68 , 69 ], and one case–control study [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 depicts the results of the systematic search and selection process, including a summary of reasons for exclusion of full text articles, which are further detailed in Supplementary File S2 . The 50 articles to inform the review included 25 quasi-experimental studies [ 2 , 7 , 8 , 9 , 10 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ], eight cross-sectional [ 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ], four randomised control trials [ 55 , 56 , 57 , 58 ], three cohort studies [ 59 , 60 , 61 ], three narrative reviews [ 62 , 63 , 64 ], three systematic reviews [ 13 , 65 , 66 ], three conference abstracts [ 67 , 68 , 69 ], and one case–control study [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…When analyzing different midsole stiffnesses on dynamic balance control, researchers found that the presence of a midsole negatively impacted balance relative to being barefoot (52). It has also been found that wearing minimalist shoes versus traditional shoes with a thicker support and a high heel has a positive influence on postural stability (9). However, a study contradicts this finding where both overall stability, as well as anterior and posterior stability, were significantly better when young adults wore athletic shoes versus those who wore minimalist or those who were barefoot (64).…”
Section: Stabilitymentioning
confidence: 99%
“…Several previous studies have reported on positive and negative influences of the type of footwear worn on postural stability, specifically among occupational footwear that is designed primarily for safety purposes rather than for optimal postural control [ 9 , 10 , 11 , 12 , 13 ]. Based on previous research, for optimal postural stability maintenance, occupational footwear, in addition to meeting safety standards, should be lighter in mass, have an elevated boot shaft, have thin and firm midsole, have a low heel height, and low heel-to-toe drop [ 14 ]. More specifically, the current research team have completed several studies and analyzed the impact of three types of occupational footwear (steel-toed work boots—ST; tactical work boots—TB; low-top slip-resistant shoes—LT) on various aspects of postural stability such as postural sway, postural response times, and muscle activity from lower extremity muscles, in non-workload conditions, as well as when exposed to both acute high-intensity and chronic low-intensity physiological workloads [ 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%